Anastatica hierochuntica (L.) methanolic and aqueous extracts exert antiproliferative effects through the induction of apoptosis in MCF-7 breast cancer cells - Saranya Rameshbabu; Safia A. Messaoudi; Zeyad Ibrahim Alehaideb; Mohammed Syed Ali; Anuradha Venktraman; Hala Alajmi; Hamad Al-Eidi; Sabine Matou-Nasri (Elsevier, 2020)
Breast cancer therapy using anticancer bioactive compounds derived from natural products as adjuvant treatment has gained recognition due to expensive and toxic conventional chemotherapeutic drugs. The whole plant of Anastatica hierochuntica (L.) (A. hierochuntica) has been investigated for its pharmacologically important anticancer properties but without categorizing the biological activities of the plant parts. We assessed the anticancer potential of different parts of A. hierochuntica (seeds, stems and leaves) and explored their mechanisms of action using the human breast cancer cell line, MCF-7. Currently, we investigated the antiproliferative effects of methanolic (MSD, MST, ML) and aqueous (ASD, AST, AL) extracts of A. hierochuntica plant parts on the MCF-7 cells using cell viability assays. Flow cytometry, Western Blot, DNA fragmentation, and gene expression assays were performed to evaluate apoptosis and cell cycle regulatory proteins. The results indicate that the methanolic and aqueous extracts decreased MCF-7 cell viability in a dose-dependent manner. The induction of apoptosis was observed in all the methanolic and aqueous-treated MCF-7 cells. The cell death process was confirmed by the visualization of DNA fragmentation and cleavage of the intrinsic apoptotic pathways, caspase-9 and caspase-3, the key enzyme causing apoptosis hallmarks. In addition, the most pro-apoptotic extracts, ASD and ML, up-regulated the expression of pro-apoptotic Bax, tumor suppressor TP53 genes and the cyclin inhibitor CDKN1A gene. In conclusion, of the aqueous and methanolic extracts of A. hierochuntica plant parts exerting antiproliferative effects through the induction of apoptosis in breast cancer MCF-7 cells, ASD and ML extracts were the most promising natural-based drugs for the treatment of breast cancer.